Sexual Experiences of Generation Z Men Living with HIV - Khalisha Ramadhini; Akhmad Faozi; Ria Inriyana (Genius Journal, 2026)
Introduction: Human Immunodeficiency Virus (HIV) remains a major public health issue, particularly among men who have sex with men (MSM). Generation Z (Gen-Z) constitutes an increasing proportion of new HIV infections and is characterized by openness toward identity, sexuality, and digital engagement. Despite this, limited research has explored the sexual experiences of HIV-positive Gen-Z individuals with homosexual orientation, especially within the Indonesian context. Understanding these experiences is crucial to addressing psychosocial needs and improving holistic care. Objective: This study aimed to explore the lived sexual experiences of HIV-positive Gen-Z patients with homosexual orientation who are undergoing antiretroviral treatment at RSUD Umar Wirahadikusumah. Method: A qualitative study with a phenomenological approach was conducted to capture participants’ subjective experiences. Three HIV-positive Gen-Z MSM receiving antiretroviral therapy were recruited using purposive sampling. Data were collected through in-depth, semi-structured interviews and analyzed using thematic analysis to identify recurring patterns and key themes. Result: Five main themes emerged from the analysis: (1) changes in the meaning of sexuality after HIV diagnosis; (2) fear of HIV transmission and rejection; (3) negotiation of sexual safety and intimacy; (4) experiences of stigma and discrimination; and (5) resilience and self-acceptance shaped by Gen-Z characteristics such as openness, authenticity, and digital literacy. Participants described significant emotional, social, and behavioral adjustments in their sexual lives influenced by health status, social responses, and access to information. Conclusion: The sexual experiences of HIV-positive Gen-Z MSM are shaped by interconnected biological, psychological, social, and generational factors. Gen-Z values contribute to adaptive coping, yet stigma remains a major challenge. These findings highlight the need for holistic, inclusive, and non-discriminatory nursing care, as well as targeted sexual health counseling and stigma-reduction interventions to improve quality of life among HIV-positive Gen-Z MSM.